The accountability information needs of key charity funders. Issue 3 (16th April 2017) - Yang, Cherrie; Northcott, Deryl; Sinclair, Rowena
Abstract : Government and philanthropic funders are key charity stakeholders, yet we know little about their accountability information needs. This New Zealand study captures these stakeholders' perceptions of the background, financial and non-financial performance information they need from charities. It also reveals how, in addition to imposing reporting requirements, these key funders engage in 'institutional work' to ensure they receive appropriate accountability information.